1969
DOI: 10.1111/j.1365-2672.1969.tb02196.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Methane‐utilizing Bacteria

Abstract: Thin sections of methane-utilizing bacteria have been examined in the electron microscope and the fine structure of the cells is described for the first time.The outstanding feature of all the isolates studied is the existence of intracellular membrane structures resembling those seen in nitrifying and photosynthetic bacteria. The possible significance of these membranes is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0
1

Year Published

1970
1970
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 14 publications
1
17
0
1
Order By: Relevance
“…116 MICROBIAL METABOLISM OF METHANE 639 see whether the particulate nature of the enzyme system catalysing the condensation offormaldehyde with pentose phosphate in P. methanica and Mtl. cap8ulatu8, as found in the present study, can be correlated with the elaborate internal membrane system found in methane-utilizing bacteria (Whittenbury, 1969;Proctor, Norris & Ribbons, 1969 …”
Section: Discussionmentioning
confidence: 70%
“…116 MICROBIAL METABOLISM OF METHANE 639 see whether the particulate nature of the enzyme system catalysing the condensation offormaldehyde with pentose phosphate in P. methanica and Mtl. cap8ulatu8, as found in the present study, can be correlated with the elaborate internal membrane system found in methane-utilizing bacteria (Whittenbury, 1969;Proctor, Norris & Ribbons, 1969 …”
Section: Discussionmentioning
confidence: 70%
“…The isolates of Whittenbury and colleagues, as well as the previous isolates, have all had an obligate requirement for methane, methanol, or dimethylether as the growth substrate. All of these methane-utilizing bacteria so far examined possess elaborate internal membrane structures when grown on methane (9,10,29,31,38,39,46). When methane utilizers are grown on methanol these internal membranes are also present, but to a lesser extent (10,38).…”
mentioning
confidence: 99%
“…partikelgebundenes Enzym handelt. Bekannt war zu diesem Zeitpunkt schon, daB Methan utilisierende Bakterien ein besonderes internes Membransystem besitzen (PROCTOR et al 1969, DAVIES u. WHITTENBURY 1970). So ist es nicht verwunderlich, daB sie dieses Membransystem mit dem Enzym, das sich auBerdem im Zellhoniogenat als labil erwies, in Zusammenhang brachten.…”
unclassified